2021
DOI: 10.1111/scs.13033
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals’ experiences with practice for managing disease‐related malnutrition in general practice and proposals for improvement: A qualitative study

Abstract: Background & Aim Disease‐related malnutrition is prevalent in all healthcare settings, including general practice, and is associated with negative consequences for the individual and the community. The aim of this study was to investigate general practitioners and general practice nurses’ perceptions of how they manage disease‐related malnutrition, and their view on introducing an early intervention against disease‐related malnutrition. Methods Content analysis was used to analyse individual semi‐structured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Mikkelsen et al analyzed individual semi-structured interviews of general practitioners and focus group interviews of clinic nurses [21]. They reported that general practices did not routinely identify disease-related malnutrition and rarely saw patients with unintended weight loss.…”
Section: Deficiencies In Nutrition Screening Parametersmentioning
confidence: 99%
“…Mikkelsen et al analyzed individual semi-structured interviews of general practitioners and focus group interviews of clinic nurses [21]. They reported that general practices did not routinely identify disease-related malnutrition and rarely saw patients with unintended weight loss.…”
Section: Deficiencies In Nutrition Screening Parametersmentioning
confidence: 99%
“…Following demographic information, the semi-structured interview guide consisted of eight overall questions aimed at clarifying the roles and responsibilities regarding early detection and treatment of DRM, communication with patients about nutrition, opportunities and tools available for guidance, collaboration with other sectors and finally barriers and facilitators for implementation of nutritional intervention [28].…”
Section: Health Professionalsmentioning
confidence: 99%
“…Based on the findings from study II, UWL is something the health professionals did not have focus on except if it is in front of the health professionals' eyes. This could be if a patient had a major and directly visible weight loss, thin patients or if the patients have other symptoms [83]. This is also found in a study from England, however the study also found that timely identification among patients at low risk need some improvements [99].…”
Section: Health Professionals' Perspective On Malnutrition and Nutrit...mentioning
confidence: 59%
“…In this section, the results and findings will be presented based on the three published papers I-III and the submitted manuscript IV. Further results and findings are described in detailed in the papers I-III (Appendix 6-8 and [82][83][84]) and manuscript IV (Appendix 9).…”
Section: Summary Of the Results And Findingsmentioning
confidence: 96%
See 1 more Smart Citation